Zjawisko seksualizacji jako wyzwanie dla współczesnej edukacji - Waszyńska, Katarzyna; Zielona-Jenek, Monika (Wydawnictwo Naukowe UAM, 2016)
Sexualization is a term that has been appearing frequently in debates in Poland in recent years. This term is used in discussions about the changes in social sexual norm, protection of the rights and freedom of the individual and the threat of sexual violence. At the same time, sexualization is a parallel area of interest for people who study human sexuality, its conditioning and changes. The aim of this article is to outline the consequences of sexualization for educational practices.
Sexualization as a Challenge for Contemporary Education
Keywords: sexualization; educational practices; human sexuality